A new species of Pachycara Zugmayer, 1911 (Teleostei: Zoarcidae) from deep-sea chemosynthetic environments in the Caribbean Sea - Anderson, M. Eric; Somerville, Russell; Copley, Jonathan T. (Zootaxa, 2016)
The 28th species of the eelpout genus Pachycara Zugmayer, 1911, is described from specimens collected from an active hydrothermal vent field at a depth of about 2300 m at the Mid-Cayman Spreading Centre of the Caribbean Sea. A tentatively identified early juvenile is recorded at a methane seep at a depth of 1049 m near Tobago. The new species is distinguished from its congeners mainly by its few pectoral fin rays, low vertebral counts, single, mediolateral branch of the lateral line system and presence of scales on the nape and cheeks.